Divided government versus incumbency externality effect: Quasi-experimental evidence on multiple voting decisions - Florian Ade; Ronny Freier (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This paper explores the interdependency of political institutions from the voter's perspective. Specifically, we are interested in three questions: (1) Does the partisan identity of the local mayor influence the voter's decision in the subsequent town council election?; (2) Does this partisan identity influence in ensuing higher level elections?; and (3) Do voters condition their vote for the mayor on the result of the last council election? We collected a unique data set for Germany in which we link election results for different political institutions at the municipal level. To identify causal effects, we rely on a regression discontinuity design focusing on close election outcomes. We find that the party of the mayor receives a bonus of 4-5 percentage points in vote share in the subsequent town council elections if, and only if, mayoral and council elections are held simultaneously. With regard to higher level elections, we find no effect for the party identity of the mayor on federal and European election outcomes. Using run-off mayor races, which are held shortly after council elections, we show that voters punish parties that performed strongly in the council election. To explain our empirical findings, we explore two mechanisms from the theoretical literature. We conclude that there is evidence both for an incumbency externality effect as well as a preference for divided government effect in opposite directions.
Keywords: H10; H11; H77; 330; regression discontinuity design; municipality data; local election results; divided government effect; incumbency externality effect; Wahlverhalten; Kommunalwahl; Politische Partei; Externer Effekt; Wahl; Deutschland